Strategic Management of Facilities, Infrastructure, and Educational Financing to Enhance Institutional Productivity: A Multiple Case Study of Pesantren-Based Vocational Schools in Indonesia - Kholik, Muhamad; Warisno, Andi; Hidayah, Nur (Universitas Islam Negeri Raden Intan Lampung, 2026)
This study examines how strategic management of facilities, infrastructure, and educational financing contributes to institutional productivity in pesantren-based vocational high schools (Sekolah Menengah Kejuruan/SMKs) in Ogan Komering Ulu Timur Regency, South Sumatra, Indonesia. Employing a qualitative multiple-case study design, data were collected through in-depth interviews, non-participant observations, and document analysis across three pesantren-based SMKs. The analysis followed an interactive model involving data condensation, data display, and conclusion drawing. The findings indicate that although existing facilities and infrastructure are generally adequate to support vocational learning, significant gaps remain, particularly in student practice rooms and industry-aligned equipment. Strategic facilities management is implemented through data-driven planning, prioritization based on institutional needs, diversification of funding sources, and efficient utilization of resources. Educational financing management emphasizes transparency, accountability, equity, and partnerships, complemented by the integration of Islamic social funding instruments such as zakat and infaq. These integrated management practices positively influence institutional productivity, reflected in improved educational input–output quality, service efficiency, organizational innovation, and stakeholder trust. The novelty of this study lies in proposing an integrated framework that combines facilities management and educational financing within the perspective of Islamic educational management, offering empirical insights into faith-based vocational education contexts that remain underexplored in international literature.